Q-Methodology and Psychological Phenotyping to Design Patient-Centered Diabetes Education for Persons With Type 2 Diabetes on Insulin Therapy. Issue 2 (April 2022) - Cha, EunSeok; Shin, Myoung Hwan; Smart, Michael; Jang, Hyesun; Lee, Jooseon; Joung, Kyong Hye; Kim, Hyun Jin; Faulkner, Melissa Spezia
Purpose: The purpose of this study was to identify the psychological phenotypes of persons with type 2 diabetes (T2D) on insulin therapy to better inform personalized diabetes education strategies to improve self-management behaviors. Methods: Q-methodology, a research approach combining the quantitative rigor of statistical analysis with qualitative data on perception of diabetes self-management by persons with T2D on insulin therapy, was used. The Summary of Diabetes Self-Care Activity measure and A1C in the past 6 months were used to further describe self-management behaviors of each P-sample, Q-sorter. Of 160 statements, 33 Q-sample statements were selected as Q-set. Then, 37 P-samples (24 men; 13 women) were recruited from a university-affiliated diabetes clinic in South Korea. Data obtained from each P-sample with a Q-set and a Q-sorting table, a forced-choice normal distribution table, were analyzed using varimax rotation. Results: Forty-one percent of the variance was explained with 5 factors represented by 27 Q-sorters, explaining variance ranging from 5% to 17% for each factor: Factor A (n = 6): those showing self-management education need but possessing inadequate health literacy; Factor B (n = 4): those valuing lifestyle modification to control diabetes; Factor C (n = 5): those valuing antidiabetic medication to control diabetes; Factor D (n = 6): carpe diem, accepting diabetes as destiny; and Factor E (n = 6): those overestimating their competencies to control diabetes. Ten Q-sorters fell into either confounded or nonsignificant. Conclusions: Tailoring messages and educational approaches based on patients' psychological phenotypes are necessary to promote optimal self-management behaviors.